Fetomaternal outcome in pregnancy with fibroid: a prospective observational study - Ahmed, Kaiser; Uzma, Syed; Gulzar, Ruby; Wani, Bilal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Uterine leiomyomas simply called as myomas, fibroids, fibroma, are benign neoplasm derived from smooth muscle cell rests of vessel wall or uterine musculature. Fibroids are rarely observed before puberty, most prevalent during reproductive age group and regress after menopause. They are oestrogen-dependent tumours, and there is evidence that leiomyomas overexpress certain estrogen and progesterone receptors when compared to normal surrounding myometrium. Methods: The present study was a prospective observational study conducted in Government Lalla Ded Hospital GMC Srinagar over a period of 18 months from May 2021 to November 2022. Results: Out of 100 patients, only 66 were delivered in our hospital while this study was being conducted. 38% patients had LSCS, 23% had normal vaginal delivery and 5% patients had vaginal delivery followed by curette. Pain was the most common antenatal complication found in 28% of patients, followed by 12% patients with malpresentation, 11% had abortion, 7% had APH and 5% patients had IUD. There was no preterm delivery or PPROM in our study. Conclusions: The present study demonstrated that the incidence of fibroids was highest in between age group of 25-34 years. The commonest type of fibroid was intramural anterior wall upper segment, followed by intramural posterior wall upper segment. Guarded pregnancy outcome was seen in multiple large fibroids in pregnancy. Cesarean section rate was on higher side especially in multiple fibroids and occupying the lower segment. Decision for cesarean myomectomy should be reserved for selected cases only where the fibroid comes in the incision site or large pedunculated fibroid. Routine cesarean myomectomy should be discouraged. To improve the neonatal outcome in pregnancies with multiple fibroids, cesarean should be done by the staff trained in delivering babies in difficult scenarios.